Discrete wavelet transform for fault types in underground distribution system - Ngaopitakkul, A.; Apisit, C. (My University, 2010)
In this paper, a technique for identifying the phase with fault appearance in underground cable is presented. The Wavelet transform has been employed to extract high frequency components superimposed on fault signals simulated using ATP/EMTP. The coefficients obtained from the Wavelet transform are used in constructing a decision algorithm. Various cases have been investigated so that the algorithm can be implemented. It is found that the proposed method can indicate the fault types with satisfactory accuracy. © 2010 American Institute of Physics.
Keywords: ATP/EMTP; Fault Types; Underground Cable; Wavelet Transform